Contractors’ Perspective on Material Waste Reduction in Kuala Lumpur - Nurul Aini, Osman; Mohd Amir Shazwan, Hashim; Jye, Hwoi Pok (UPM Press, 2017)
In the area of sustainable development, construction waste is an important issue that must be tackled responsibly. It is an assortment of waste, at the stage of construction. This paper assesses waste minimisation or reduction measures and such practices in the Kuala Lumpur construction industry. A structured questionnaire survey was conducted to obtain contractors’ views on 25 waste minimisation measures discussed in literature. Data was analysed using frequency analysis method and average index analysis method. The results showed that adoption of proper site management techniques is widely practised. The adoption of these waste minimisation measures could lead cost savings to the construction industry and prevent environmental degradation